MORTALITY PATTERN IN BUFFALO CALVES IN ORGANIZED FARMS OF TAMIL NADU - Kumar, Vasantha; Sivakumar, T; Ramesh, V; Edwin, SC (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The mortality pattern in Murrah and Surti buffalo calves was studied for a period of 11 years (1991- 2001) from the available records in certain organized farms of Tamil Nadu for four seasons viz. hot, south west monsoon, northeast monsoon and cold seasons. Data pertaining to 471 death records of buffalo calves were collected and analyzed. High (P
Keywords: Mortality pattern; Buffalo calves; seasons